Many LINE1 elements contribute to the transcriptome of human somatic cells - Rangwala, Sanjida H; Zhang, Lili; Kazazian, Haig H (Genome biology, 2009)
Background While LINE1 (L1) retroelements comprise nearly 20% of the human genome, the majority are thought to have been rendered transcriptionally inactive, due to either mutation or epigenetic suppression. How many L1 elements 'escape' these forms of repression and contribute to the transcriptome of human somatic cells? We have cloned out expressed sequence tags corresponding to the 5' and 3' flanks of L1 elements in order to characterize the population of elements that are being actively transcribed. We also examined expression of a select number of elements in different individuals. Results We isolated expressed sequence tags from human lymphoblastoid cell lines corresponding to 692 distinct L1 element sites, including 410 full-length elements. Four of the expression tagged sites corresponding to full-length elements from the human specific L1Hs subfamily were examined in European-American individuals and found to be differentially expressed in different family members. Conclusions A large number of different L1 element sites are expressed in human somatic tissues, and this expression varies among different individuals. Paradoxically, few elements were tagged at high frequency, indicating that the majority of expressed L1s are transcribed at low levels. Based on our preliminary expression studies of a limited number of elements in a single family, we predict a significant degree of inter-individual transcript-level polymorphism in this class of sequence.